Effect of fasting on the structure and function of the gastrointestinal tract of house sparrows (Passer domesticus) - Chediack, Juan Gabriel (2012)
Starvation is a condition that often affects animals in nature. The gastrointestinal tract is the organ system displaying the most rapid and dramatic changes in response to nutrient deprivation. To date, little is known about starvation phases and effects on the organ morphology and digestive function in small passerine birds. In this study, we determined the phases of starvation and examined the effect of final stage of starvation in the organ morphology and, intestinal histology and enzymatic function in the small intestine. Our results show the three phases of the classical model of fasting in a shorter period of time. The mass of heart, pancreas, stomach, small intestine and liver of long-term fasted birds was reduced between 20 and 47%. The mass decrease in small intestine was correlated with reduction in small intestinal histology: perimeter, mucosal thickness, villus height and width. In contrast, the enzyme activity of sucrase-isomaltase and aminopeptidase-N in enterocytes, all expressed per mug of protein, was higher in long-term fasted birds than fed animals. This suggest that, while autophagy of digestive organs is induced by starvation, consistent with phenotypic plasticity, the activity of sucrase-isomaltase and aminopeptidase-N remains high, probably as an anticipatory strategy to optimize digestion at re-feeding time.